Biometric and engineering properties of garlic for mechanical harvesting - KHAMBE VISHAL K.; DIPANKAR D.E.; P.K. SAHOO; S.K. JHA (Seed Research, 2026)
Design of crop production and processing equipment requires biometric and engineering properties of relevant crop. Garlic (Allium sativum) is the second most important bulbous crop from Alliaceae family after onion. Some biometric and engineering properties of garlic were evaluated as a function of moisture content. The number of leaves per plant at its harvesting stage ranged between 5 to 7 with modal value of 5 at all three levels of plant moisture content. Length of garlic plant and its weight decreased from 696-684 mm and 39.57-34.71 g, respectively, as the plant moisture content decreased from 42.38 - 36.21% (db). Polar diameter, equatorial diameter and shape factor of garlic bulb increased from 36.72 - 40.49 mm, 34.07-37.95 mm and 0.91 - 0.94, respectively, with same decrease in plant moisture content. Angle of rolling resistance increased from 22.64° - 35.64°, while crushing resistance and cutting resistance of garlic plant increased from 463.86 - 544.06 N and 218.40 - 268.60 N, respectively, with decrease of plant moisture content from 42.38 - 36.21% (db). These values are essential for design of mechanical harvester for garlic.